2003
DOI: 10.1002/ceat.200301816
|View full text |Cite
|
Sign up to set email alerts
|

Gas Holdup and Volumetric Mass Transfer Coefficient in a Slurry Bubble Column

Abstract: The gas holdup, e, and volumetric mass transfer coefficient, k L a, were measured in a 0.051 m diameter glass column with ethanol as the liquid phase and cobalt catalyst as the solid phase in concentrations of 1.0 and 3.8 vol.-%. The superficial gas velocity U was varied in the range from 0 to 0.11 m/s, spanning both the homogeneous and heterogeneous flow regimes. Experimental results show that increasing catalyst concentration decreases the gas holdup to a significant extent. The volumetric mass transfer coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 6 publications
3
20
0
Order By: Relevance
“…2 shows the measured gas holdup for varying slurry concentrations. Addition of catalyst particles tends to reduce the gas holdup, e G , to a significant extent, consistent with earlier work in cylindrical bubble columns [8,14]. The reduction in gas holdup with increasing e S is due to a decrease in the small bubble population.…”
Section: Resultssupporting
confidence: 83%
“…2 shows the measured gas holdup for varying slurry concentrations. Addition of catalyst particles tends to reduce the gas holdup, e G , to a significant extent, consistent with earlier work in cylindrical bubble columns [8,14]. The reduction in gas holdup with increasing e S is due to a decrease in the small bubble population.…”
Section: Resultssupporting
confidence: 83%
“…16. The estimated volumetric mass transfer coefficient has a good agreement with experimental values shown in literatures (Prakash and Bendale, 1991;Behkish et al, 2002;Vandu and Krishna, 2003). Figure 7.13 shows the effect of water in synthesis gas fed into reactor.…”
Section: Computational Results and Discussionsupporting
confidence: 82%
“…Degaleesan et al (1997) measured eddy diffusivities using computer aided radioactive particle tracking (CARPT) in air-water system for slurry bubble column reactor. Behkish et al (2002), Kluytmans et al (2003) and Vandu and Krishna (2003) measured mass transfer coefficients in slurry bubble column of three-phase flows including small particles. We have developed a mathematical model to describe the hydrodynamics of slurry bubble column reactors (Gamwo et al, 2003.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of the mass transfer study results in the literature indicates that there are mixed results reported regarding the dependence of k L on U G . Some researchers found k L to be independent of U G [31][32][33][34]. Gopal and Sharma [35] found k L to decrease slightly with U G [12] while Lemoine et al [35] and Mena et al [36] found k L to increase with U G .…”
Section: Effect Of Distributorsmentioning
confidence: 99%